Iodine Content of Household Salt and Urinary Iodine of Primary School Pupils in Commercial Towns in Nsukka Senatorial Zone, Enugu State, Nigeria - Edith U., Madukwe; Peace N., Ani; Adimoranma, Maduabuchi (Pakistan Journal of Nutrition, 2013)
This study was designed to determine the iodine content of household salt and urinary iodine of primary school pupils in commercial towns in Nsukka Senatorial Zone, Enugu State, Nigeria. Two commercial towns (Orba and Ibagwa-aka) in Nsukka senatorial district were purposely selected. Iodine content of salt was measured at household level as well the nutritional iodine status of 200 school aged children (6-12 years) was assessed by measuring their urinary iodine concentration. Validated questionnaire was used to test the Knowledge, Attitude, Practice and Behaviour (KAPB) of 40 household salt consumers and 15 salt retailers in the two communities. Statistical Package for Social Sciences (SPSS) version 17 was used to analyze the data into frequencies, percentages and mean. More than half (58.3%) of the household salt at Orba and 70% at Ibagwa-aka were iodized to an adequate level of > 15 ppm, while 12.5% at Orba and 3.7% at Ibagwa-aka, had no iodine (0 ppm). The proportions of the primary school children that were mildly iodine deficient at Orba and Ibagwa-aka were 43.3 and 56.2%, respectively. The factors that affect the iodine status of school children in the study areas include poor use of salt, unhygienic method of handling and storage of salt and cultural practices. There is need to increase awareness of both the retailers and consumers in Orba and Ibagwa-aka regarding the consequences of poor use, unhygienic handling and storage of salt.